(untitled) (Revista Inclusiones, 2020)
The modern economy development and the constantly growing competitive struggle require the search for new, more efficient strategic opportunities for enterprises. Due to this, improvement of the enterprise management methods is of particular relevance, as it defines the enterprise’s belonging to an innovation-driven economy, where the competitiveness of enterprises and the economy are generally determined by the level of innovation and the degree of intellectual development based on knowledge and information.